International taxation principles in the context of financial security of Ukraine - O.Y. Yurkivskyi; O.V. Lytvynchuk (Економіка, управління та адміністрування)
Tax principles have been determining approaches to the construction of the tax system and tax policy of governments around the world for a long time. Transforming with due regard to exogenous and endogenous factors, tax principles are aimed at ensuring the fullest possible replenishment of the state budget revenues and fulfillment of government functions, as well as at supporting a financial state based on the established tax trust. The problems of tax evasion at the level of a single state and the expansion of the activities of individuals and legal entities at the international level have led to the unification of efforts of the international community on the basis of bilateral agreements and the activities of international organizations. Thanks to international organizations the principles of tax transparency have been discussed and approved, and should be applied by governments around the world in building trust between taxpayers and governments. The principles are divided into several groups to maximize the consideration of the state and peculiarities of the functioning of a particular tax system, harmonize tax rules and instruments to support international tax relations, and create preconditions for minimizing tax evasion schemes in the course of foreign economic activity of residents and non-residents. International taxation principles are of a recommendatory nature, and to ensure financial security and control, functioning of tax relations of a particular country, its own tax principles, formed and harmonized over time, are used on the basis of theoretical and practical research of scientists of different economic directions and schools. The security situation on the European continent requires an increase in funding for the armed forces of European countries, which requires governments to ensure tax transparency and taxpayer confidence both in a particular country and internationally.